Content Analysis of Environmental Education Textbooks for Junior High Using Beck and McKeown Model - Dwi Pujiastuti; Dian Nurmala (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
One of the supporting factors for the success of the teaching and learning process is the content delivered by the teacher. Regarding this content, teachers need guidance through textbooks. Therefore, this research is necessary to determine the quality of textbooks in order to support the learning process and help enhance higher-order thinking skills, one of which is critical thinking. This study aims to analyze the content of the Environmental Education textbook used by junior high school students and teachers in South Tangerang City. This research employs a descriptive analysis method. The textbook content is analyzed using the cognitive development model by Beck, McKeown, and Kucan, which has been modified into five analytical steps. The results show that the Environmental Education textbook contains many activities that can help students improve their critical thinking and problem-solving skills. Referring to the cognitive development criteria by Beck and McKeown, the textbook can be categorized as excellent, as it does not merely present data and facts to be memorized, but provides meaningful learning content. This condition is expected to improve junior high school students’ thinking and problem-solving abilities, particularly concerning Environmental Education issues.